Les attitudes d'apprenants taiwanais de langue étrangère à l'égard de la bande dessinée et quelques implications - Sossouvi, Laurent-Fidèle (Linguistik Online, 2012)
The issue of exploitation foreign languages' instructional comics has been widely discussed in recent years. However, although the authors indicate its advantages and its great educational potential, few have actually investigated learners' attitudes towards this learning resource. And everyone knows the importance of affective factors in the process of learning foreign languages. In addition, comic is rarely used as a teaching aid in Asia. As part of this contribution exploratory, we propose to examine not only the attitudes of Sinophones Learners of French as Foreign Language towards comic, but also the support it can provide. To achieve this goal, fifty-five Taiwanese learners, from level A1 to B1, divided into three distinct groups were probed, questioned and subjected to work around comics. According to the results, we conclude that (i) learners have positive attitudes towards comics, mangas, and are highly motivated; (ii) the use of comics has helped to improve their language skills and intercultural learning as well as revitalize the target language. Implications of these findings are discussed.